Measurement and correlation of physical properties of aqueous solutions of tetrabutylammonium hydroxide, piperazine and their aqueous blends - Safdar, R. (Chemical Industry Press, 2015)
The density, viscosity and refractive index of aqueous solutions of tetrabutylammonium hydroxide (TBAOH), piperazine (PZ) and their aqueous blends are determined at several temperatures (303.15 to 333.15 K). All these measured physicochemical properties decreases with an increase in temperature. The density data is used to calculate the coefficient of thermal expansion and excess molar volume of all aqueous binary and ternary solutions. The coefficient of thermal expansion increases with increase in temperatures and concentrations. The negativity of excess molar volume for all the aqueous solution decreased with increase in temperature. Each physical property is correlated with temperature by least square method and the corresponding coefficients for each property are presented. The prediction values from correlations for the physical properties are in good agreement with the experimental values. Â© 2015 The Chemical Industry and Engineering Society of China, and Chemical Industry Press. All rights reserved.